Battery insulating member made of polyphenylene sulfide resin composition and manufacturing method thereof

A polyphenylene sulfide resin composition with an organic silane compound addresses hydrofluoric acid resistance and weld part toughness, ensuring effective insulation and moldability for battery insulating materials, particularly in high-temperature conditions.

JP7600563B2Active Publication Date: 2024-12-17TORAY INDUSTRIES INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020140802
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-24
Publication Date
2024-12-17
Estimated Expiration
2040-08-24

AI Technical Summary

Technical Problem

Existing battery insulating materials face challenges with hydrofluoric acid resistance, weld part toughness, and heat resistance, particularly in high-temperature environments, and their manufacturing methods are either costly or less productive than injection molding.

Method used

A polyphenylene sulfide resin composition containing a polyphenylene sulfide resin and an organic silane compound, optimized for injection molding, which provides excellent hydrofluoric acid resistance, caulking resistance, and weld part toughness, with specific molecular weight and viscosity ranges to ensure moldability.

Benefits of technology

The composition achieves high tensile elongation and strength in hydrofluoric acid exposure, maintains weld part integrity under deformation, and ensures effective insulation even at elevated temperatures, enhancing safety and productivity in battery manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600563000005
    Figure 0007600563000005
  • Figure 0007600563000001
    Figure 0007600563000001
  • Figure 0007600563000002
    Figure 0007600563000002
Patent Text Reader

Abstract

To provide an insulating member for a battery made of a polyphenylene sulfide resin composition that combines excellent hydrofluoric acid resistance and resistance to clamping.SOLUTION: The insulating member for a battery consists of a polyphenylene sulfide resin composition containing (a) a polyphenylene sulfide resin and (b) an organosilane compound. A test piece (ISO527-2-1A) obtained by injection molding the resin composition has a tensile breaking elongation of 5% or more in a tensile test (ISO527-1,2) after immersion in hydrofluoric acid (50% aqueous solution) for 500 hours under 60°C conditions.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an insulating member for a battery made of a polyphenylene sulfide resin composition having excellent resistance to hydrofluoric acid, resistance to crimping, toughness of welds, and heat resistance. [Background technology]

[0002] Batteries are provided with various insulating members for the purpose of preventing internal short circuits. Conventional insulating members have been made of polyolefin resins such as polyethylene resin and polypropylene resin, which have electrolyte resistance and toughness, in order to ensure safety during actual use. In recent years, due to the miniaturization of electronic devices and the spread of electric vehicles, the capacity and energy density of secondary batteries in particular have been increased. Therefore, in secondary batteries, insulating members are exposed to higher temperatures when abnormalities occur, and insulating members are also required to have heat resistance. In this context, there is a demand for the creation of insulating members such as insulating plates made of new resin materials that combine toughness, high-temperature rigidity, moldability, and heat resistance, instead of polyolefin resins such as polyethylene resin and polypropylene resin. For example, Patent Document 1 describes an insulating member made of a phenolic resin laminated plate with a glass cloth base material and containing inorganic additives as an insulating plate, which suppresses the hardening and shrinkage of the phenolic resin due to heat during overcharging and prevents deformation of the electrode plate group consisting of the positive electrode plate, the negative electrode plate, and the separator.

[0003] On the other hand, in lithium ion secondary batteries, as described in, for example, Patent Document 2, a mixed solvent of a cyclic carbonate such as propylene carbonate or ethylene carbonate and a chain carbonate such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate is generally used as a non-aqueous electrolyte, and a fluorine compound such as LiPF6 or LiBF4 is used as a supporting salt. However, when a fluorine compound is used, it reacts with a small amount of moisture in the battery to generate hydrofluoric acid (HF), which causes a problem that the generated HF deteriorates surrounding components including insulating components. For this reason, for example, Patent Document 3 describes a sealing gasket made of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) that has excellent resistance to non-aqueous electrolytes and resistance to hydrofluoric acid.

[0004] In addition, injection molding, which is excellent in mass productivity, is widely used as a manufacturing method for insulating members for batteries. However, since insulating members such as insulating plates have openings or through holes for fitting terminals, when molding by injection molding, two or more resin flows are generated in the annular cavity, and weak weld lines are generated where these resin flows join together. For example, as described in Patent Document 4, it is known that in the manufacturing process of batteries, a so-called "crimping process" is performed in which the joint is pressed or tightened when insulating members such as insulating plates are fitted together. However, when insulating members or gaskets having welded parts are crimped, there is a problem that cracks occur in the welded parts due to the load, and they do not function as insulating members or gaskets. In addition, the welded parts cannot follow the deformation of the insulating members due to the swelling of the battery caused by the increase in internal pressure that occurs when the battery is used, and cracks or breaks occur in the welded parts, which may not function as insulating members or gaskets. In response to this, Patent Document 4 describes a manufacturing method for a gasket that does not generate weld lines by cutting and flaring a cylindrical body obtained by extrusion molding.

[0005] Furthermore, Patent Document 5 describes a manufacturing process in which a sheet of PFA is punched out into a molded product shape, and then subjected to hot and cold pressing. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2002-231314 A [Patent Document 2] Japanese Patent Application Publication No. 8-321326 [Patent Document 3] JP 2006-147159 A [Patent Document 4] JP 2007-48582 A [Patent Document 5] International Publication No. 2014 / 129413 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the material described in Patent Document 1 has a problem in that it does not have resistance to hydrofluoric acid. In addition, although no welds are formed because it is produced by punching, it has a problem in terms of productivity because it is produced by impregnating a glass cloth substrate with phenolic resin, heating and curing it to produce a laminate, and then punching is performed.

[0008] Patent documents 3 to 5 all use PFA resin, which is an expensive resin, and are therefore undesirable from a cost perspective. Also, the manufacturing method described in Patent document 4 involves a process of forming a gasket shape after obtaining a cylindrical molded product by extrusion molding, and therefore no welds are formed, but is less preferable from the viewpoint of productivity than injection molding.

[0009] In addition, the manufacturing method described in Patent Document 5 involves producing a sheet, punching it out into a molded product, and then subjecting it to hot and cold pressing processes, so no welds are produced. However, this method is less preferable in terms of productivity than injection molding. [Means for solving the problem]

[0010] As a result of investigations aimed at solving such problems, the present inventors have found that a polyphenylene sulfide resin composition containing (a) a polyphenylene sulfide resin and (b) an organosilane compound exhibits excellent resistance to hydrofluoric acid, and have found that an insulating member such as an insulating plate using the resin composition has excellent chemical resistance, crimping resistance, weld toughness, and heat resistance. That is, the present invention has been made to solve at least a part of the above-mentioned problems, and can be carried out in the following forms. (1) An insulating material for a battery, the insulating material comprising a polyphenylene sulfide resin composition containing (a) a polyphenylene sulfide resin and (b) an organosilane compound, the resin composition being injection molded into a test piece (ISO527-2-1A), which is immersed in hydrofluoric acid (50% aqueous solution) at 60°C for 500 hours and then subjected to a tensile test (ISO527-1,2) to have a tensile breaking elongation of 5% or more. (2) The insulating material for a battery according to (1), wherein a test piece (ISO527-2-1A) obtained by injection molding the resin composition has a weight change rate of 2% or less before and after immersion in hydrofluoric acid (50% aqueous solution) at 60°C for 500 hours. (3) The insulating member for a battery according to (1) or (2), wherein a test piece obtained by injection molding the resin composition has a thickness of 1.6 mm, a width of 6 mm, and a gauge length of 50 mm, and has a weld formed in the center between the gauge lines. In a tensile test carried out at 23°C and a tensile speed of 10 mm / min, the tensile product, which is expressed by the area under the curve of the stress-strain curve, is 100 MPa % or more. (4) The insulating member for a battery according to any one of (1) to (3), wherein a test piece obtained by injection molding the resin composition has a thickness of 1.6 mm, a width of 6 mm and a gauge length of 50 mm, and has a weld formed in the center between the gauge lines. In a tensile test carried out at 23°C and at a tensile speed of 10 mm / min, the insulating member for a battery has a tensile breaking elongation of 3.0% or more. (5) The insulating member for a battery according to any one of (1) to (4), wherein a test piece obtained by injection molding the resin composition and having a weld formed in the center between the marked lines has a tensile strength of 45 MPa or more when subjected to a tensile test in an atmosphere at 80°C. (6) An insulating member for a battery according to any one of (1) to (5), wherein the resin composition contains less than 1 part by weight of (c) a polyolefin monomer or polyolefin copolymer containing 80 wt% or more of an olefin component per 100 parts by weight of (a) PPS resin. (7) The insulating member for a battery according to any one of (1) to (6), wherein the resin composition has a melt viscosity (measurement conditions: temperature 320°C, shear rate 2432 / s) of 250 Pa·s or less. (8) An insulating member for a battery according to any one of (1) to (7), wherein in a molecular weight distribution obtained by measuring the resin composition by gel permeation chromatography (GPC), a proportion of components detected earlier than an elution time corresponding to a polystyrene-equivalent molecular weight of 750,000 is 0.4 to 8.5%, and a weight average molecular weight of components detected later than an elution time corresponding to a polystyrene-equivalent molecular weight of 750,000 is 50,000 to 95,000. (9) The insulating member for a battery according to any one of (1) to (8), wherein the proportion of the polyphenylene sulfide resin (a) in the resin composition is 95% by weight or more. (10) The insulating member for a battery according to any one of (1) to (9), which has a weld line. (11) A method for producing an insulating member for a battery according to any one of (1) to (10), comprising injection molding the resin composition. Effect of the Invention

[0011] According to the present invention, it is possible to obtain an insulating member for a battery made of a polyphenylene sulfide resin composition having excellent resistance to hydrofluoric acid, chemical resistance, crimping resistance, toughness of welds, and heat resistance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram of a molded product used in evaluating caulking resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail.

[0014] (1)(a) Polyphenylene sulfide resin The (a) PPS resin used in the present invention is a polymer having a repeating unit represented by the following structural formula:

[0015] [ka]

[0016] From the viewpoint of heat resistance, it is preferable for the polymer to contain 70 mol % or more, and more preferably 90 mol % or more, of the repeating unit represented by the above structural formula. In addition, about 30 mol % or less of the repeating units of the (a) PPS resin may be composed of repeating units having the following structure.

[0017] [ka]

[0018] A PPS copolymer partially having such a structure has a melting point lower than the general melting point of PPS, 280° C., and therefore such a resin composition is advantageous in terms of moldability.

[0019] The weight average molecular weight of the (a) PPS resin used in the present invention is not particularly limited, but in terms of obtaining better mechanical properties, the weight average molecular weight is preferably 30,000 to 150,000, more preferably 40,000 to 130,000, more preferably 45,000 to 110,000, and even more preferably 50,000 to 90,000. If the weight average molecular weight is small, the mechanical properties of the PPS resin itself will decrease, so a weight average molecular weight of 30,000 or more is preferable. On the other hand, if the weight average molecular weight exceeds 150,000, the melt viscosity will increase significantly, which tends to be undesirable in molding processing.

[0020] The weight average molecular weight in the present invention is a value calculated in terms of polystyrene using a gel permeation chromatography (GPC) manufactured by Senshu Scientific.

[0021] A method for producing the (a) PPS resin used in the present invention will be described below, but the method is not limited to the method described below as long as the (a) PPS resin having the above-mentioned properties can be obtained.

[0022] First, the polyhalogenated aromatic compound, sulfidizing agent, polymerization solvent, molecular weight regulator, polymerization aid and polymerization stabilizer used in the production method will be described.

[0023] [Polyhalogenated aromatic compounds] Polyhalogenated aromatic compounds refer to compounds having two or more halogen atoms in one molecule.Specific examples of polyhalogenated aromatic compounds include p-dichlorobenzene, m-dichlorobenzene, o-dichlorobenzene, 1,3,5-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2,4,5-tetrachlorobenzene, hexachlorobenzene, 2,5-dichlorotoluene, 2,5-dichloro-p-xylene, 1,4-dibromobenzene, 1,4-diiodobenzene, and 1-methoxy-2,5-dichlorobenzene, and preferably p-dichlorobenzene. In addition, for the purpose of introducing a carboxyl group, a carboxyl group-containing dihalogenated aromatic compound such as 2,4-dichlorobenzoic acid, 2,5-dichlorobenzoic acid, 2,6-dichlorobenzoic acid, or 3,5-dichlorobenzoic acid, or a mixture thereof, can be used as a copolymerization monomer in one preferred embodiment. Although it is also possible to combine two or more different polyhalogenated aromatic compounds to form a copolymer, it is preferable to use a p-dihalogenated aromatic compound as the main component.

[0024] The amount of the polyhalogenated aromatic compound used, in order to obtain a PPS resin (a) having a viscosity suitable for processing, can be, for example, in the range of 0.9 to 2.0 mol, preferably 0.95 to 1.5 mol, and more preferably 1.005 to 1.2 mol, per mol of the sulfidizing agent.

[0025] [Sulfidizing agent] The sulfidizing agent includes alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide.

[0026] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these, with sodium sulfide being preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.

[0027] Specific examples of the alkali metal hydrosulfide include sodium hydrosulfide, potassium hydrosulfide, lithium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these, with sodium hydrosulfide being preferred. These alkali metal hydrosulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.

[0028] In addition, an alkali metal sulfide prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide can also be used.Alkali metal sulfide can also be prepared from an alkali metal hydrosulfide and an alkali metal hydroxide, and then transferred to a polymerization tank for use.

[0029] Alternatively, an alkali metal sulfide prepared in situ in the reaction system from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide can be used.Alkaline metal sulfides can also be prepared from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide, and then transferred to a polymerization tank for use.

[0030] When a part of the sulfidizing agent is lost before the start of the polymerization reaction due to a dehydration operation or the like, the amount of the charged sulfidizing agent means the remaining amount obtained by subtracting the lost amount from the actual charged amount.

[0031] It is also possible to use an alkali metal hydroxide and / or an alkaline earth metal hydroxide together with the sulfidizing agent.Specific examples of the alkali metal hydroxide include, for example, sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide, and mixtures of two or more of these.Specific examples of the alkaline earth metal hydroxide include, for example, calcium hydroxide, strontium hydroxide, barium hydroxide, etc., and among these, sodium hydroxide is preferably used.

[0032] When an alkali metal hydrosulfide is used as the sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide simultaneously. The amount of the alkali metal hydroxide used is, for example, in the range of 0.95 to 1.20 mol, preferably 1.00 to 1.15 mol, and more preferably 1.005 to 1.100 mol per mol of the alkali metal hydrosulfide.

[0033] [Polymerization solvent] As the polymerization solvent, it is preferable to use an organic polar solvent. Specific examples include N-alkylpyrrolidones such as N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone, caprolactams such as N-methyl-ε-caprolactam, aprotic organic solvents such as 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, dimethylsulfone, and tetramethylene sulfoxide, and mixtures thereof, all of which are preferably used because of their high reaction stability. Among these, N-methyl-2-pyrrolidone (hereinafter sometimes abbreviated as NMP) is particularly preferably used.

[0034] The amount of the organic polar solvent used is selected from the range of 2.0 to 10 moles, preferably 2.25 to 6.0 moles, and more preferably 2.5 to 5.5 moles, per mole of the sulfidizing agent.

[0035] [Molecular weight regulator] A monohalogen compound (which does not necessarily have to be an aromatic compound) can be used in combination with the polyhalogenated aromatic compound in order to form terminals in the resulting (a) PPS resin or to adjust the polymerization reaction or molecular weight.

[0036] [Polymerization aid] In order to obtain a (a) PPS resin having a relatively high degree of polymerization in a short time, it is also a preferred embodiment to use a polymerization aid. Here, the polymerization aid means a substance that has the effect of increasing the viscosity of the (a) PPS resin obtained. Specific examples of such polymerization aids include organic carboxylates, water, alkali metal chlorides, organic sulfonates, alkali metal sulfates, alkaline earth metal oxides, alkali metal phosphates, and alkaline earth metal phosphates. These can be used alone or in combination of two or more. Among them, organic carboxylates, water, and alkali metal chlorides are preferred, and alkali metal carboxylates are more preferred as organic carboxylates, and lithium chloride is more preferred as alkali metal chlorides.

[0037] The above alkali metal carboxylate has the general formula R(COOM) n (wherein R is an alkyl group, a cycloalkyl group, an aryl group, an alkylaryl group, or an arylalkyl group having 1 to 20 carbon atoms; M is an alkali metal selected from lithium, sodium, potassium, rubidium, and cesium; and n is an integer of 1 to 3). The alkali metal carboxylate can also be used as a hydrate, anhydride, or an aqueous solution. Specific examples of the alkali metal carboxylate include lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, sodium benzoate, sodium phenylacetate, potassium p-toluate, and mixtures thereof.

[0038] The alkali metal carboxylate may be formed by adding and reacting an organic acid with one or more compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates in approximately equal chemical equivalents. Among the above alkali metal carboxylates, lithium salts have high solubility in the reaction system and have a large auxiliary effect, but are expensive, while potassium, rubidium, and cesium salts are thought to have insufficient solubility in the reaction system, so sodium acetate, which is inexpensive and has moderate solubility in the polymerization system, is most preferably used.

[0039] When these alkali metal carboxylates are used as polymerization aids, the amount used is usually in the range of 0.01 mol to 2 mol per mol of the charged alkali metal sulfide. In terms of obtaining a higher degree of polymerization, the amount used is preferably in the range of 0.1 mol to 0.6 mol, and more preferably in the range of 0.2 mol to 0.5 mol.

[0040] When water is used as a polymerization aid, the amount added is usually in the range of 0.3 mol to 15 mol per mol of the charged alkali metal sulfide, and in terms of obtaining a higher degree of polymerization, the range of 0.6 mol to 10 mol is preferable, and the range of 1 mol to 5 mol is more preferable.

[0041] Of course, two or more of these polymerization aids can be used in combination. For example, when an alkali metal carboxylate and water are used in combination, a higher molecular weight can be achieved with a smaller amount of each.

[0042] The timing of addition of these polymerization aids is not particularly specified, and they may be added at any time during the pre-step, at the start of polymerization, or during the polymerization, as described below, or may be added in several portions, but when an alkali metal carboxylate is used as the polymerization aid, it is more preferable to add it at the start of the pre-step or at the start of polymerization, because it is easy to add it. When water is used as the polymerization aid, it is effective to add it during the polymerization reaction after the polyhalogenated aromatic compound is charged.

[0043] [Polymerization stabilizer] A polymerization stabilizer can be used to stabilize the polymerization reaction system and prevent side reactions. The polymerization stabilizer contributes to the stabilization of the polymerization reaction system and suppresses undesirable side reactions. One of the indicators of side reactions is the generation of thiophenol, and the addition of a polymerization stabilizer can suppress the generation of thiophenol. Specific examples of polymerization stabilizers include compounds such as alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, and alkaline earth metal carbonates. Among them, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. The above-mentioned alkali metal carboxylates also act as polymerization stabilizers. In addition, when an alkali metal hydrosulfide is used as a sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide at the same time, as mentioned above, but an alkali metal hydroxide that is in excess of the sulfidizing agent can also serve as a polymerization stabilizer.

[0044] These polymerization stabilizers can be used alone or in combination of two or more. The polymerization stabilizer is preferably used in a ratio of usually 0.02 to 0.2 mol, preferably 0.03 to 0.1 mol, more preferably 0.04 to 0.09 mol, per mol of the charged alkali metal sulfide. If this ratio is too small, the stabilizing effect is insufficient, and conversely, if it is too large, it is economically disadvantageous and the polymer yield tends to decrease.

[0045] The timing of adding the polymerization stabilizer is not particularly specified, and it may be added at any time during the pre-step described below, at the start of polymerization, or during the polymerization, or may be added in several divided portions. However, it is more preferable to add it simultaneously at the start of the pre-step or at the start of polymerization from the viewpoint of ease.

[0046] Next, a preferred method for producing the PPS resin (a) used in the present invention will be specifically described in order, including a pre-process, a polymerization reaction process, a recovery process, and a post-treatment process, although the method is not limited to this method.

[0047] [Pre-process] (a) In the production process for PPS resin, the sulfidizing agent is usually used in the form of a hydrate. It is preferable to heat a mixture containing an organic polar solvent and a sulfidizing agent and remove excess water from the system before adding a polyhalogenated aromatic compound.

[0048] As described above, the sulfidizing agent may be prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide, or in a tank separate from the polymerization tank. There is no particular restriction on this method, but a preferable method is to add an alkali metal hydrosulfide and an alkali metal hydroxide to an organic polar solvent in an inert gas atmosphere at room temperature to 150°C, preferably from room temperature to 100°C, and then heat the mixture to at least 150°C or higher, preferably 180 to 260°C, under normal pressure or reduced pressure, to distill off water. A polymerization aid may be added at this stage. Toluene or the like may be added to promote the distillation of water.

[0049] In the polymerization reaction, the amount of water in the polymerization system is preferably 0.3 to 10.0 mol per 1 mol of the charged sulfidizing agent. Here, the amount of water in the polymerization system is the amount of water charged to the polymerization system minus the amount of water removed from the polymerization system. The charged water may be in any form such as water, an aqueous solution, or crystal water.

[0050] [Polymerization reaction process] (a) PPS resin is produced by reacting a sulfidizing agent with a polyhalogenated aromatic compound in an organic polar solvent at a temperature range of 200° C. or higher and lower than 290° C.

[0051] When starting the polymerization reaction process, the organic polar solvent, the sulfidizing agent, and the polyhalogenated aromatic compound are mixed, desirably in an inert gas atmosphere, at a temperature range of room temperature to 240° C., preferably 100° C. to 230° C. A polymerization aid may be added at this stage. The order of charging these raw materials may be random, or they may be charged simultaneously.

[0052] The mixture is usually heated to a temperature in the range of 200° C. to less than 290° C. There are no particular limitations on the heating rate, but a rate of 0.01 to 5° C. / min is usually selected, and a range of 0.1 to 3° C. / min is more preferable.

[0053] In general, the temperature is finally raised to 250 to less than 290° C., and the reaction is carried out at that temperature for usually 0.25 to 50 hours, preferably 0.5 to 20 hours.

[0054] In order to obtain a higher degree of polymerization, it is effective to react at 200° C. to 260° C. for a certain period of time before the final temperature is reached, and then to raise the temperature to 270° C. to less than 290° C. In this case, the reaction time at 200° C. to 260° C. is usually selected within the range of 0.25 hours to 20 hours, and preferably 0.25 hours to 10 hours.

[0055] In order to obtain a polymer with a higher degree of polymerization, it may be effective to carry out the polymerization in multiple stages. When carrying out the polymerization in multiple stages, it is effective to carry out the polymerization when the conversion rate of the polyhalogenated aromatic compound in the system at 245°C reaches 40 mol% or more, preferably 60 mol%.

[0056] The conversion rate of polyhalogenated aromatic compounds (abbreviated as PHA here) is a value calculated by the following formula: The amount of remaining PHA can usually be determined by gas chromatography.

[0057] (A) When a polyhalogenated aromatic compound is added in excess of an alkali metal sulfide in terms of molar ratio Conversion rate=[charged amount of PHA (mol)−remaining amount of PHA (mol)] / [charged amount of PHA (mol)−excess amount of PHA (mol)].

[0058] (B) Cases other than (A) above Conversion rate=[charged amount of PHA (mol)−remaining amount of PHA (mol)] / [charged amount of PHA (mol)].

[0059] [Recovery process] In the (a) PPS resin manufacturing method, after the polymerization is completed, solid matter is recovered from the polymerization reaction product containing the polymer, the solvent, etc. As for the recovery method, it is essential to adopt a method of recovering the particulate polymer by slowly cooling after the polymerization reaction is completed. The cooling speed is not particularly limited, but is usually about 0.1°C / min to 3°C / min. It is not necessary to slowly cool at the same speed throughout the entire cooling process, and a method of slowly cooling at a speed of 0.1 to 1°C / min until the polymer particles crystallize and precipitate, and then at a speed of 1°C / min or more may be adopted.

[0060] [Post-processing process] The (a) PPS resin may be produced through the above-mentioned polymerization and recovery steps, and then may be subjected to acid treatment, hot water treatment, washing with an organic solvent, or treatment with an alkali metal or alkaline earth metal.

[0061] The acid treatment is carried out as follows: There are no particular limitations on the acid used in the acid treatment of the (a) PPS resin so long as it does not have the effect of decomposing the (a) PPS resin, and examples of the acid include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid, and propylic acid, and among these, acetic acid and hydrochloric acid are more preferably used, but acids such as nitric acid that decompose and deteriorate the (a) PPS resin are undesirable.

[0062] The acid treatment may be carried out by immersing the PPS resin (a) in an acid or an aqueous solution of an acid, and may be carried out with appropriate stirring or heating, if necessary. For example, when acetic acid is used, a sufficient effect can be obtained by immersing the PPS resin powder in an aqueous solution of pH 4 heated to 80 to 200°C and stirring for 30 minutes. The pH after the treatment may be 4 or higher, for example, about pH 4 to 8. The PPS resin (a) that has been subjected to the acid treatment is preferably washed several times with water or warm water to remove the remaining acid or salt. The water used for washing is preferably distilled water or deionized water, so as not to impair the effect of the preferable chemical modification of the PPS resin (a) by the acid treatment.

[0063] The hot water treatment is carried out as follows: When the (a) PPS resin is subjected to hot water treatment, the temperature of the hot water is preferably 100° C. or higher, more preferably 120° C. or higher, still more preferably 150° C. or higher, and particularly preferably 170° C. or higher. If the temperature is less than 100° C., the desired chemical modification effect of the (a) PPS resin is small, which is not preferred.

[0064] In order to achieve the desired chemical modification effect of the (a) PPS resin by hot water washing, it is preferable that the water used is distilled water or deionized water. There are no particular limitations on the procedure for the hot water treatment, and it can be carried out by adding a specified amount of (a) PPS resin to a specified amount of water, heating and stirring in a pressure vessel, or by continuously carrying out hot water treatment. The ratio of (a) PPS resin to water is preferably higher, but a bath ratio of 200 g or less of (a) PPS resin to 1 liter of water is usually selected.

[0065] In addition, since decomposition of the terminal groups is undesirable, it is desirable to carry out the treatment in an inert atmosphere to avoid this. Furthermore, after the hot water treatment, the (a) PPS resin is preferably washed several times with warm water to remove any remaining components.

[0066] When washing with an organic solvent, the procedure is as follows. The organic solvent used for washing the (a) PPS resin is not particularly limited as long as it does not have the action of decomposing the (a) PPS resin, and examples thereof include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, 1,3-dimethylimidazolidinone, hexamethylphosphoramide, and piperazinones, sulfoxide-sulfone solvents such as dimethylsulfoxide, dimethylsulfone, and sulfolane, ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, and acetophenone, dimethyl ether, dipropyl ether, dioxane, and tetrahydrofuran. Examples of the organic solvent include ether solvents such as hydrofuran, halogen-based solvents such as chloroform, methylene chloride, trichloroethylene, ethylene dichloride, perchloroethylene, monochloroethane, dichloroethane, tetrachloroethane, perchloroethane, and chlorobenzene, alcohol-phenol solvents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol, propylene glycol, phenol, cresol, polyethylene glycol, and polypropylene glycol, and aromatic hydrocarbon solvents such as benzene, toluene, and xylene. Among these organic solvents, N-methyl-2-pyrrolidone, acetone, dimethylformamide, and chloroform are particularly preferred. These organic solvents are used alone or in combination of two or more.

[0067] The method of washing with an organic solvent includes immersing the (a) PPS resin in the organic solvent, and stirring or heating can be performed as necessary. There is no particular restriction on the washing temperature when washing the (a) PPS resin with an organic solvent, and any temperature between room temperature and about 300°C can be selected. The higher the washing temperature, the higher the washing efficiency tends to be, but usually a washing temperature between room temperature and 150°C is sufficient to obtain the desired effect. Washing can also be performed under pressure in a pressure vessel at a temperature above the boiling point of the organic solvent. There is also no particular restriction on the washing time. Although it depends on the washing conditions, in the case of batch washing, washing for 5 minutes or more usually obtains the desired effect. Continuous washing is also possible.

[0068] Examples of the method of alkali metal or alkaline earth metal treatment include a method of adding an alkali metal salt or alkaline earth metal salt before, during, or after the previous step, a method of adding an alkali metal salt or alkaline earth metal salt into a polymerization vessel before, during, or after the polymerization step, or a method of adding an alkali metal salt or alkaline earth metal salt at the beginning, middle, or end of the washing step. The easiest method among them is a method of adding an alkali metal salt or alkaline earth metal salt after removing residual oligomers and residual salts by washing with an organic solvent or washing with warm or hot water. The alkali metal or alkaline earth metal is preferably introduced into PPS in the form of an alkali metal ion or alkaline earth metal ion such as acetate, hydroxide, or carbonate. Excess alkali metal salt or alkaline earth metal salt is preferably removed by washing with warm water or the like. The concentration of the alkali metal ion or alkaline earth metal ion when introducing the alkali metal or alkaline earth metal is preferably 0.001 mmol or more per 1 g of PPS, more preferably 0.01 mmol or more. The temperature is preferably 50° C. or higher, more preferably 75° C. or higher, and particularly preferably 90° C. or higher. There is no particular upper limit to the temperature, but from the viewpoint of operability, it is usually preferably 280° C. or lower. The bath ratio (weight of cleaning solution relative to the weight of dry PPS) is preferably 0.5 or higher, more preferably 3 or higher, and even more preferably 5 or higher.

[0069] In the present invention, from the viewpoint of obtaining a polyphenylene sulfide resin composition excellent in retention stability, a method in which residual oligomers and residual salts are removed by repeatedly washing with an organic solvent and with warm water of about 80° C. or the above-mentioned hot water several times, and then the method in which the resin is treated with an acid, an alkali metal salt, or an alkaline earth metal salt is treated is preferred, and in particular a method in which the resin is treated with an alkali metal salt or an alkaline earth metal salt is more preferred.

[0070] In addition, the (a) PPS resin can also be used after being polymerized by a thermal oxidative crosslinking treatment in which heating is performed in an oxygen atmosphere after polymerization or by heating with the addition of a crosslinking agent such as a peroxide, thereby increasing the molecular weight.

[0071] When dry heat treatment is performed for the purpose of increasing the molecular weight by thermal oxidation crosslinking, the temperature is preferably 160 to 260°C, more preferably 170 to 250°C. The oxygen concentration is desirably 5% by volume or more, more desirably 8% by volume or more. There is no particular upper limit to the oxygen concentration, but the limit is about 50% by volume. The treatment time is preferably 0.5 to 100 hours, more preferably 1 to 50 hours, and even more preferably 2 to 25 hours. The heat treatment device may be a normal hot air dryer, or a rotary or stirring blade-equipped heating device, but in the case of efficient and more uniform treatment, it is more preferable to use a rotary or stirring blade-equipped heating device.

[0072] Dry heat treatment can also be performed to suppress thermal oxidative crosslinking and remove volatiles. The temperature is preferably 130 to 250°C, more preferably 160 to 250°C. In this case, the oxygen concentration is preferably less than 5% by volume, and even less than 2% by volume. The treatment time is preferably 0.5 to 50 hours, more preferably 1 to 20 hours, and even more preferably 1 to 10 hours. The heat treatment device may be a normal hot air dryer, or a rotary or stirring blade-equipped heating device, but in the case of efficient and more uniform treatment, it is more preferable to use a rotary or stirring blade-equipped heating device.

[0073] However, from the viewpoint of exhibiting excellent toughness, the (a) PPS resin of the present invention is preferably a substantially linear PPS resin that has not been subjected to high molecular weight by thermal oxidative crosslinking treatment, or a semi-crosslinked PPS resin that has been lightly oxidative crosslinked, and is more preferably a substantially linear PPS resin. In the present invention, a mixture of (a) PPS resins having different melt viscosities may be used.

[0074] In a preferred embodiment, the (a) PPS resin of the present invention contains 25 to 400 μmol / g of carboxyl groups from the viewpoint of improving the reactivity with the (b) organosilane compound. The carboxyl group content is more preferably 25 to 250 μmol / g, more preferably 30 to 150 μmol / g, and even more preferably 30 to 80 μmol / g. If the amount of carboxyl groups in the PPS resin is less than 25 μmol / g, the reactivity with the (b) organosilane compound tends to decrease, which is not preferred. On the other hand, if the amount of carboxyl groups in the PPS resin exceeds 400 μmol / g, the amount of volatile components increases during the processing step, which is not preferred.

[0075] Examples of methods for introducing a carboxyl group into the (a) PPS resin include a method of copolymerizing a polyhalogenated aromatic compound containing a carboxyl group, and a method of adding a compound containing a carboxyl group, such as maleic anhydride or sorbic acid, and reacting it with the (a) PPS resin while melt-kneading it to introduce the carboxyl group.

[0076] (2)(b) Organosilane compounds It is essential that the PPS resin composition constituting the battery insulating member of the present invention contains (b) an organic silane compound. Specific examples of the organic silane compound include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, mercapto group-containing alkoxysilane compounds such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, ureido group-containing alkoxysilane compounds such as γ-ureidopropyltriethoxysilane, γ-ureidopropyltrimethoxysilane, and γ-(2-ureidoethyl)aminopropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropylmethyldimethoxysilane, and γ-isocyanatepropyltriethoxysilane. Examples of the organic silane compounds include isocyanate group-containing alkoxysilane compounds such as isocyanate propyl methyl diethoxysilane, γ-isocyanate propyl ethyl dimethoxysilane, γ-isocyanate propyl ethyl diethoxysilane, and γ-isocyanate propyl trichlorosilane, and amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl) aminopropyl methyl dimethoxysilane, γ-(2-aminoethyl) aminopropyl trimethoxysilane, and γ-aminopropyl trimethoxysilane, and among them, from the viewpoint of reactivity, epoxy group-containing alkoxysilane compounds, amino group-containing alkoxysilane compounds, and isocyanate-containing alkoxysilane compounds are preferred, and isocyanate group-containing alkoxysilane compounds are particularly preferred. Excellent reactivity means that it leads to the development of excellent toughness after hydrofluoric acid treatment.

[0077] The amount of the organosilane compound added is preferably 0.2 to 5 parts by weight, particularly preferably 0.2 to 3 parts by weight, relative to 100 parts by weight of the total PPS resin composition. More preferably, it is 0.2 to 2 parts by weight. When the amount of the organosilane compound added is 0.2 parts by weight or more, excellent toughness after hydrofluoric acid treatment can be sufficiently obtained, and the occurrence of burrs and mold staining during molding can be suppressed. By setting the amount of the organosilane compound to 5 parts by weight or less, the toughness improvement effect can be obtained, while the amount of gas generation can be suppressed, so that mold staining does not occur, and a significant increase in melt viscosity can also be suppressed, so that even a thin-walled insulating member for a battery can be easily injection molded, which is preferable.

[0078] (3)(c) Polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin components In the PPS resin composition constituting the insulating member for a battery of the present invention, the content of (c) a polyolefin monomer or polyolefin copolymer containing 80 wt % or more of an olefin component is preferably less than 1 part by weight.

[0079] For example, blending polyethylene as a polyolefin monomer improves mold releasability during injection molding, shortening the molding cycle and improving moldability. On the other hand, if the blending amount is 1 part by weight or more, it is not preferable because it leads to gas generation and mold contamination during molding. Examples of polyolefin monomers include alkene polymers such as polypropylene, polybutylene, polyisobutylene, polypentene, and polymethylpentene in addition to polyethylene.

[0080] In addition, in general, in order to improve the toughness of (a) PPS resin, a thermoplastic elastomer, which is a type of polyolefin copolymer, is blended. However, in the present invention, it is preferable to avoid blending the polyolefin copolymer as much as possible in order to obtain good crimping resistance, toughness at the welds, and moldability. The polyolefin copolymer exists as an island component in the sea phase made of PPS resin, but it is thought that the presence of resin components other than the PPS resin that form the island components contributes to a decrease in adhesion at the welds and leads to a decrease in toughness, so it is preferable to blend the amount of (c) component in the above range.

[0081] Examples of such polyolefin copolymers include ethylene-butene copolymers, ethylene-propylene copolymers, ethylene-hexene copolymers, ethylene-octene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-glycidyl methacrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-styrene copolymers, ethylene-methyl acrylate-glycidyl methacrylate copolymers, ethylene-ethyl acrylate-glycidyl methacrylate copolymers, ethylene-vinyl acetate-glycidyl methacrylate copolymers, and the like.

[0082] In a preferred embodiment, the polyolefin copolymer used in the present invention contains a reactive functional group (a) from the viewpoint of forming an intermolecular bond with the PPS resin.

[0083] The reactive functional group possessed by the polyolefin copolymer is not particularly limited, and specific examples thereof include a vinyl group, an epoxy group, a carboxyl group, an acid anhydride group, an ester group, an aldehyde group, a carbonyldioxy group, a haloformyl group, an alkoxycarbonyl group, an amino group, a hydroxyl group, a styryl group, a methacryl group, an acrylic group, a ureido group, a mercapto group, a sulfide group, an isocyanate group, and a hydrolyzable silyl group. Among these, a hydroxyl group, an epoxy group, a carboxyl group, an amino group, an acid anhydride group, and an isocyanate group are preferred, and the copolymer may contain two or more types of these reactive functional groups.

[0084] In the present invention, the content of (c) polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin component is preferably less than 1 part by weight, more preferably less than 0.8 parts by weight, and even more preferably less than 0.5 parts by weight, based on 100 parts by weight of (a) polyphenylene sulfide resin. It is particularly preferable not to mix polyolefin copolymer. If the content of polyolefin copolymer exceeds 1 part by weight, the amount of volatile components increases when the PPS resin composition is heated and melted, which is undesirable from the viewpoint of electrolyte resistance and molding processability.

[0085] (4)(d) Other additives Furthermore, the PPS resin composition constituting the insulating member for a battery of the present invention may contain resins other than (a) the PPS resin and (c) the polyolefin monomer or polyolefin copolymer containing 80 wt% or more of an olefin component, as long as the effects of the present invention are not impaired.

[0086] Specific examples of such resins include, but are not limited to, polyamide, polybutylene terephthalate, polyethylene terephthalate, polyketone, liquid crystal polymer, polyether ketone, polyether ether ketone, and fluororesin (polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), and polychlorotrifluoroethylene (PCTFE)). The amount of such resins added is preferably less than 15 parts by weight, more preferably less than 10 parts by weight, and particularly preferably less than 5 parts by weight, based on 100 parts by weight of the total PPS resin composition. It is considered that the presence of resin components other than the PPS resin that becomes the island component contributes to a decrease in adhesion at the welds and leads to a decrease in toughness, so the amount of other resins added is preferably within the above range.

[0087] In the PPS resin composition constituting the insulating member for batteries of the present invention, the amount of phosphorus oxoacid metal salt blended is preferably less than 0.01 parts by weight, more preferably less than 0.005 parts by weight, per 100 parts by weight of (a) PPS resin. Blending of phosphorus oxoacid metal salt can suppress oxidative decomposition of (c) polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin component, and can suppress mold fouling during molding processing, while a blending amount of 0.01 parts by weight or more significantly increases the melt viscosity of the PPS resin composition, which is undesirable for molding processing of insulating members for batteries having a thin wall shape. It is most preferable that the composition does not contain phosphorus oxoacid metal salt.

[0088] Examples of phosphorus oxoacid metal salts include hypophosphorous acid, phosphorous acid, phosphoric acid, phosphinic acid, phosphonic acid, diphosphoric acid, and triphosphoric acid.Specific examples include potassium hypophosphite, sodium hypophosphite, calcium hypophosphite, potassium phosphinate, sodium phosphinate, calcium phosphinate, aluminum phosphinate, aluminum diethylphosphinate, zinc phosphinate, and magnesium phosphinate.

[0089] In addition, for the purpose of modification, the following compounds can be added. Plasticizers such as polyalkylene oxide oligomer compounds, thioether compounds, ester compounds, and organic phosphorus compounds, crystal nucleating agents such as organic phosphorus compounds and polyether ether ketones, metal soaps such as montanic acid waxes, lithium stearate and aluminum stearate, release agents such as ethylenediamine-stearic acid-sebacic acid polycondensates and silicone compounds, and other usual additives such as water, lubricants, ultraviolet inhibitors, coloring inhibitors, colorants, and foaming agents can be blended. If any of the above compounds exceeds 10 parts by weight of the total composition, the inherent properties of the PPS resin composition of the present invention are impaired, which is not preferable, and it is preferable to add 5 parts by weight or less, more preferably 1 part by weight or less.

[0090] In the present invention, a compatibilizer can be used in combination to improve the compatibility between the resins. Specific examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, brominated epoxy resins, bifunctional epoxy resins having a special skeleton such as a biphenyl skeleton or a naphthalene skeleton, glycidyl ether type epoxy resins such as multifunctional epoxy resins such as cresol novolac type, trisphenol methane type, and dicyclopentadiene type, glycidyl amine type epoxy resins such as aromatic amine type and aminophenol type, and glycidyl ester type epoxy resins such as hydrophthalic acid type and dimer acid type.

[0091] The amount of such epoxy resin added is preferably 0.1 to 5 parts by weight, and particularly preferably 0.2 to 3 parts by weight, per 100 parts by weight of the total PPS resin composition.

[0092] Although not an essential component, the PPS resin composition constituting the battery insulating member of the present invention may contain an inorganic filler within a range that does not impair the effects of the present invention. Specific examples of such inorganic fillers include fibrous fillers such as glass fibers, carbon fibers, carbon nanotubes, carbon nanohorns, potassium titanate whiskers, zinc oxide whiskers, calcium carbonate whiskers, wollastonite whiskers, aluminum borate whiskers, aramid fibers, alumina fibers, silicon carbide fibers, ceramic fibers, asbestos fibers, gypsum fibers, and metal fibers; fullerenes, talc, wollastonite, zeolite, sericite, mica, kaolin, clay, pyrophyllite, silica, bentonite, asbestos, and silicates such as alumina silicate; silicon oxides; Metal compounds such as magnesium oxide, alumina, zirconium oxide, titanium oxide, and iron oxide, carbonates such as calcium carbonate, magnesium carbonate, and dolomite, sulfates such as calcium sulfate and barium sulfate, hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, glass beads, glass flakes, glass powder, ceramic beads, boron nitride, silicon carbide, carbon black, and non-fibrous fillers such as silica and graphite are used, and among them, glass fiber, silica, and calcium carbonate are preferred, and calcium carbonate and silica are particularly preferred from the viewpoint of corrosion prevention and lubricant effects. These inorganic fillers may be hollow, and two or more types may be used in combination. These inorganic fillers may be pretreated with coupling agents such as isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds, and epoxy compounds before use. Among them, calcium carbonate, silica, and carbon black are preferred from the viewpoint of corrosion prevention and lubricant effects.

[0093] The amount of the inorganic filler is selected to be less than 30 parts by weight, preferably less than 10 parts by weight, more preferably less than 5 parts by weight, and even more preferably 1 part by weight or less, relative to 100 parts by weight of the total PPS resin composition. There is no particular lower limit, but 0.0001 parts by weight or more is preferred. While the incorporation of an inorganic filler is effective in improving the strength of the material, an incorporation of more than 30 parts by weight is not preferred because it reduces toughness.

[0094] (5) Method for producing resin composition As a method for producing the PPS resin composition constituting the insulating member for a battery of the present invention, production in a molten state or production in a solution state can be used, but from the viewpoint of simplicity, production in a molten state is preferably used. For production in a molten state, melt kneading by an extruder or melt kneading by a kneader can be used, but from the viewpoint of productivity, melt kneading by an extruder capable of continuous production is preferably used. For melt kneading by an extruder, at least one extruder such as a single screw extruder, a twin screw extruder, a multi-screw extruder such as a four-screw extruder, or a twin-screw single screw composite extruder can be used, but from the viewpoint of kneading property, reactivity, and productivity improvement, a multi-screw extruder such as a twin screw extruder or a four-screw extruder can be preferably used, and melt kneading by a twin screw extruder is most preferable.

[0095] A more specific method of melt kneading is not necessarily limited to this, but it is preferable to use a twin-screw extruder having an L / D (L: screw length, D: screw diameter) of 10 or more, preferably 20 or more, and having two or more kneading sections, preferably three or more. There is no particular upper limit to L / D, but 60 or less is preferable from the viewpoint of economic efficiency. There is also no particular upper limit to the number of kneading sections, but 10 or less is preferable from the viewpoint of productivity. The ratio of the kneading section to the entire screw length is preferably 15% or more, more preferably 20% or more, and even more preferably 30% or more. If the ratio of the kneading section to the entire screw length is less than 15%, the kneading power is poor, so that the number average dispersion diameter of (c) polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin component becomes coarse, and it is difficult to express the desired physical properties. On the other hand, the upper limit of the ratio of the kneading section to the entire screw length is preferably 70% or less from the viewpoint of preventing deterioration of the resin due to the occurrence of excessive shear heat generation during kneading.

[0096] The screw rotation speed is preferably 150 to 1000 rpm, more preferably 300 to 1000 rpm, and even more preferably 350 to 800 rpm. When the screw rotation speed exceeds 150 rpm, the kneading force is sufficient, so that (c) the number average dispersion diameter of the polyolefin monomer or polyolefin copolymer containing 80 wt% or more of an olefin component becomes fine, leading to the development of the desired toughness. (b) Even when an organic silane compound is added, the reaction occurs sufficiently, leading to the development of the desired toughness and mold fouling properties. When the screw rotation speed exceeds 1000 rpm, deterioration of the resin and additives occurs due to excessive shear heat generation during kneading, leading to a decrease in toughness, a decrease in mold fouling properties, and a decrease in melt viscosity, leading to a decrease in moldability such as the generation of burrs. In addition, by setting the screw rotation speed to a high value within this range, the melt viscosity can be reduced while maintaining toughness, which improves the flowability during injection molding of the insulating member for a battery, which is a thin-walled shape, and is a favorable tendency from the viewpoint of moldability.

[0097] The preferred cylinder temperature (°C) range is +5 to +100°C relative to the melting point of (a) PPS resin, which is 250 to 280°C, and more specifically, is in the range of 280 to 400°C, more preferably in the range of 280 to 360°C, and even more preferably in the range of 280 to 330°C.

[0098] The order of mixing the raw materials when melt-kneading is not particularly limited, and any of the following methods may be used: a method in which all the raw materials are mixed and then melt-kneaded by the above-mentioned method; a method in which a portion of the raw materials are mixed and then melt-kneaded by the above-mentioned method, and then the remaining raw materials are mixed and melt-kneaded; or a method in which a portion of the raw materials are mixed and then the remaining raw materials are mixed using a side feeder while being melt-kneaded by a twin-screw extruder.

[0099] (6) PPS resin composition The PPS resin composition constituting the insulating member for batteries of the present invention is characterized in that the tensile elongation at break in a tensile test (ISO527-1, 2) after immersing a test piece (ISO527-2-1A) obtained by injection molding in hydrofluoric acid (50% aqueous solution) for 500 hours under 60°C conditions is 5% or more (experimental conditions are 23°C, tensile speed 50mm / min, and chuck distance 114mm). 6% or more is more preferable, and 7% or more is even more preferable. The tensile elongation at break in the tensile test after immersion in hydrofluoric acid of the test piece being 5% or more means that the insulating member for batteries made of the PPS resin composition has excellent resistance to hydrofluoric acid, and even if exposed to hydrofluoric acid generated during practical use of the insulating member for batteries, deterioration of the material can be suppressed and insulation properties can be maintained, which is essential from the viewpoint of ensuring safety. The higher the upper limit of the tensile elongation at break in the tensile test after immersion in hydrofluoric acid, the more preferable it is, and there is no particular limit, but the upper limit is practically about 200%. In order to obtain a PPS resin composition having such a tensile elongation at break after immersion in hydrofluoric acid, a method of adding an organosilane compound to the PPS resin or a method of adding as few components as possible other than the organosilane compound can be mentioned as a preferred method.

[0100] The PPS resin composition constituting the insulating member for a battery of the present invention preferably has a tensile product represented by the area under the curve of the stress-strain curve of 100 MPa·% or more in a tensile test performed on a test piece obtained by injection molding, which has a thickness of 1.6 mm, a width of 6 mm, and a gauge length of 50 mm and has a weld formed in the center between the gauge lines (hereinafter, a tensile test using a test piece having such a weld may be referred to as a weld tensile test). More preferably, the tensile product is 100 MPa·% or more, more preferably 150 MPa·% or more, and even more preferably 200 MPa·% or more. The tensile product is represented by the area under the curve of the stress-strain curve in a tensile test, and can be used as the strain fracture energy up to the breaking point in the tensile test, and is a so-called toughness index. Specifically, for example, the tensile product can be calculated by integrating the stress value in the elongated state for each elongation rate of 0.04% for the area under the curve of the stress-strain curve. A tensile product of 100 MPa·% or more in a weld tensile test means that the toughness of the weld portion is excellent, and when the weld is formed into an insulating material for a battery, it is preferable from the viewpoint of ensuring safety because it can suppress breakage during the crimping process in battery manufacturing and during actual use and maintain insulation. The upper limit of the tensile product in a weld tensile test is preferably a higher value, and there is no particular restriction, but the practical upper limit is about 1000 MPa·%. In order to obtain a PPS resin composition having such a tensile product, a method of adding an organosilane compound to the PPS resin or a method of adding as few components as possible other than the organosilane compound can be exemplified as a preferred method.

[0101] The PPS resin composition constituting the insulating member for a battery of the present invention has a tensile breaking elongation (%) of 3.0% or more, preferably 4.0% or more, and more preferably 5.0% or more, in a tensile test performed at 23°C and a tensile speed of 10 mm / min on a test piece having a thickness of 1.6 mm, a width of 6 mm, and a gauge length of 50 mm obtained by injection molding and a weld portion formed in the center between the gauge lines. The tensile breaking elongation of 3.0% or more in the weld tensile test means that the toughness of the weld portion is excellent, and when the weld is formed into the shape of an insulating member for a battery, breakage is suppressed when a load is applied and the weld is stretched in the crimping process during battery production, which is preferable from the viewpoint of improving the yield in the production process and ensuring safety in the actual use environment. The higher the elongation, the more preferable the upper limit of the tensile breaking elongation in the weld tensile test. There is no particular restriction, but the upper limit is practically about 100%. The tensile strength in the same test is preferably 60 MPa or more, more preferably 65 MPa or more, and even more preferably 70 MPa or more. A tensile strength of 60 MPa or more in a weld tensile test means that damage to the weld, which is the weakest part of a molded product, can be suppressed, and is preferable because it allows for the design of parts to be made thinner and more complex. The upper limit of the tensile strength in a weld tensile test is preferably high, and there is no particular limit, but the practical upper limit is about 300 MPa.

[0102] The PPS resin composition constituting the insulating member for a battery of the present invention preferably has a tensile strength of 45 MPa or more, more preferably 50 MPa or more, in a tensile test performed on a test piece obtained by injection molding, with a thickness of 1.6 mm, a width of 6 mm, and a gauge length of 50 mm, and a weld portion formed in the center between the gauge lines, at an 80°C atmosphere and a tensile speed of 10 mm / min. A tensile strength of 45 MPa or more in a weld tensile test in an 80°C atmosphere is preferable because the strength as an insulating member for a battery is maintained even in a high-temperature environment during actual use of the battery, and deformation and breakage are suppressed. The upper limit of the tensile strength in a weld tensile test in an 80°C atmosphere is preferably high, and there is no particular limit, but the practical upper limit is about 200 MPa.

[0103] The melt viscosity (temperature 320°C, shear rate 2432 / s) of the PPS resin composition constituting the battery insulating member of the present invention is preferably 250 Pa·s or less, more preferably 200 Pa·s or less, and even more preferably 180 MPa. A melt viscosity of 250 Pa·s or less is preferable from the viewpoint of moldability of the battery insulating member having a thin wall shape. If the melt viscosity exceeds 250 Pa·s, it leads to a decrease in moldability. The lower limit of the melt viscosity is preferably 10 Pa·s or more because it leads to the generation of burrs during molding. In order to obtain a PPS resin composition having such a melt viscosity, a method of using a PPS resin having a molecular weight in a specific range as a raw material or a method of kneading the PPS resin and the organosilane compound at a high rotation speed during melt kneading can be exemplified.

[0104] In addition, the fluidity of the PPS resin composition constituting the insulating member for a battery of the present invention is such that the flow length in a spiral flow mold (1 mm thickness, cylinder temperature 320°C, mold temperature 140°C, injection speed 230 mm / sec, injection pressure 98 MPa, injection time 5 sec, cooling time 15 sec) is preferably 100 mm or more, more preferably 115 mm or more, and even more preferably 130 mm or more. The larger this value, the better the fluidity. A flow length of 100 mm or more is preferable from the viewpoint of the molding processability of the insulating member for a battery, which has a thin wall shape. If the flow length is less than 100 mm, it leads to a decrease in molding processability. The upper limit of the flow length is preferably as high as possible, and there is no particular restriction, but the upper limit is practically about 300 mm.

[0105] In the PPS resin composition constituting the insulating member for a battery of the present invention, in the molecular weight distribution obtained by measuring the resin composition by gel permeation chromatography (GPC), the proportion of a component (hereinafter sometimes referred to as component (X)) detected earlier than the elution time corresponding to the molecular weight of 750000 in terms of polystyrene is preferably 0.4 to 8.5%, and the weight average molecular weight of a component (hereinafter sometimes referred to as "component (Y)") detected later than the elution time corresponding to the molecular weight of 750000 in terms of polystyrene is preferably 50000 to 95000. By setting the proportion of component (X) and the weight average molecular weight of component (Y) within the above range, it is possible to achieve both excellent toughness of the insulating member for a battery and melt viscosity suitable for molding into a thin shape, which is preferable. The proportion of component (X) is preferably 0.5 to 8.0%, more preferably 0.5 to 7.5%. The weight average molecular weight of component (Y) is preferably 60000 to 90000, more preferably 65000 to 85000. The proportion of component (X) and the weight average molecular weight of component (Y) are both indicators of the amount of high molecular weight material produced by the reaction in the extruder. If the proportion of component (X) exceeds 8.5%, the reaction between the PPS resin and the components other than the PPS resin contained therein will be excessive, resulting in a significant increase in melt viscosity, which will lead to a decrease in molding processability. If it is less than 0.4%, it will be difficult to achieve the desired toughness, and it will lead to the occurrence of burrs during molding process and mold staining due to low molecular weight components. If the weight average molecular weight of component (Y) is less than 50,000, it means that the molecular weight of the PPS resin in the PPS resin composition is too small, making it difficult to achieve the desired toughness, and if it exceeds 95,000, it means that the molecular weight of the PPS resin in the PPS resin composition is too large, which means that the melt viscosity is high, which will lead to a decrease in molding processability. In order to set the proportion of component (X) and the weight average molecular weight of component (Y) within the above ranges, a method can be exemplified in which PPS resin and an organosilane compound are melt-kneaded using a twin-screw extruder at a high rotation speed using a PPS resin having a weight average molecular weight of 50,000 to 90,000.

[0106] Here, "the proportion of components detected earlier than the elution time corresponding to a molecular weight of 750,000" refers to the proportion of the area of ​​the area corresponding to components having a polystyrene-equivalent molecular weight of 750,000 or more, when the total area of ​​the GPC elution curve is taken as 100%.

[0107] In the PPS resin composition constituting the insulating member for a battery of the present invention, the proportion of the PPS resin (a) in the PPS resin composition is preferably 95% by weight or more, more preferably 97% by weight or more, and even more preferably 98% by weight or more, from the viewpoints of toughness of the weld portion and moldability.

[0108] (7) Battery insulating materials The insulating member for a battery made of the PPS resin composition of the present invention refers to an insulating member for a primary or secondary battery, and is used to prevent an internal short circuit between a pair of terminals in a primary or secondary battery. Examples of the primary or secondary battery include primary batteries such as an alkaline manganese dry battery, a galvanic battery, a nickel-based primary battery, a lithium battery, a manganese dry battery, a mercury battery, and an all-solid-state battery, and secondary batteries such as a lead-acid battery, a lithium-air battery, a lithium-ion secondary battery, a lithium-ion polymer secondary battery, a lithium iron phosphate ion battery, a lithium-sulfur battery, a nickel-cadmium storage battery, a nickel-hydrogen rechargeable battery, a nickel-lithium battery, a nickel-zinc battery, and an all-solid-state battery.

[0109] Examples of insulating members for batteries include insulating plates, gaskets, terminal holders, cases, insulating rings, insulating tubes, etc. Since the insulating member for batteries made of the PPS resin composition of the present invention has excellent toughness even in welds formed by injection molding or the like, the risk of breakage occurring in the welds can be significantly reduced, and therefore application to insulating plates, gaskets, terminal holders, and cases is preferable, and application to insulating plates is particularly preferable from the viewpoint of the risk of direct internal short circuit.

[0110] The insulating member for a battery of the present invention can be molded by various molding methods such as injection molding, extrusion molding, compression molding, blow molding, and injection compression molding, among which injection molding is preferred from the viewpoint of productivity. However, when the insulating member for a battery is molded by injection molding, a ring-shaped flow of molten resin occurs at an opening where a terminal or a lid is inserted, and a weak part called a weld is formed at the part where two or more resin flows join. When manufacturing a battery, a fitting process is provided in which the positive and negative terminals of the battery, the lid, and the gasket or insulating plate are assembled, and the fitting is performed using a so-called "crimping process" in which the joints are hammered or tightened. However, when an insulating plate or gasket having a weld part obtained by the injection molding method is used, the load on the molded product in the crimping process during fitting may cause a crack in the weld part, and the insulating plate or gasket may not function as it should. For such manufacturing processes, the present invention has discovered that when a battery insulating material has a weld portion, the tensile product (strain fracture energy) characteristics that prevent breakage even when the weld portion follows deformation such as stretching are important.

[0111] It is preferable that an insulating member such as an insulating plate made of the PPS resin composition of the present invention has excellent crimping resistance. The crimping resistance can be evaluated by the following method. An insulating member for a battery having an opening as shown in FIG. 1 is injection molded by injection molding, and the insulating member for a battery is bent 90 degrees with the weld line as the center line, and the damage state is evaluated according to the following criteria, which is used as an index of crimping resistance. When 10 specimens are evaluated, a level of zero breaks and cracks is judged as ◎, a level of zero breaks and one or more but three or less cracks is judged as ○, a level of zero breaks and four or more but ten or less cracks is judged as △, and a specimen in which even one specimen breaks is judged as ×.

[0112] The insulating member for a battery made of the PPS resin composition of the present invention has excellent resistance to hydrofluoric acid. The resistance to hydrofluoric acid can be evaluated as follows. A test piece (ISO527-2-1A) is molded by injection molding, and immersed in hydrofluoric acid (50% aqueous solution) at 60°C for 500 hours. The weight change rate before and after immersion is calculated and evaluated using the following formula. The weight change rate is calculated and evaluated as an absolute value. Weight change rate (%) = |(weight of molded product after treatment - weight of molded product before treatment) / weight before treatment| x 100 (%) The weight change rate before and after immersion in hydrofluoric acid is preferably 2% or less, more preferably 1.5% or less, and even more preferably 1.2% or less. A weight change rate of 2% or less before and after immersion in hydrofluoric acid is preferable from the viewpoint of suppressing deterioration of the insulating material for a battery. If the weight change rate before and after immersion in hydrofluoric acid exceeds 2%, deterioration, decomposition or swelling of the resin material occurs, which means that the mechanical properties as a structural member for a battery are reduced, and this is not preferable. The lower limit of the weight change rate before and after immersion in hydrofluoric acid is preferably as small as possible, and there is no particular restriction, but the lower limit is practically about 0.001%. EXAMPLES

[0113] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. Here, Examples 1 to 6 are examples of the present invention, and the rest are reference examples.

[0114] In the examples and comparative examples, the following were used: (a) PPS resin, (b) organosilane compound, (c) polyolefin monomer or polyolefin copolymer containing 80 wt % or more of an olefin component, and (d) other additives.

[0115] [(a) PPS resin (a-1, a-2)] a-1: Linear PPS resin Weight average molecular weight: 70,000, Number average molecular weight: 23,000, Carboxyl group amount: 33 μmol / g, Melting point: 280°C a-2: Linear PPS resin Weight average molecular weight: 42000, Number average molecular weight: 16000, Carboxyl group amount: 42μmol / g, Melting point: 280℃

[0116] [(b) Organosilane compounds (b-1, b-2, b-3)] b-1: γ-isocyanate propyl triethoxysilane (Shin-Etsu Chemical Co., Ltd., KBE-9007N). b-2: γ-aminopropyltriethoxysilane (Shin-Etsu Chemical Co., Ltd., KBE-903) b-3: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-303)

[0117] [(c) Polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin component (c-1, c-2)] c-1: Polyethylene (Prime Polymer, PE7000FP), melting point 130°C c-2: Ethylene-glycidyl methacrylate copolymer (Sumitomo Chemical Co., Ltd. olefin resin, Bondfast E, melting point 103°C, MFR: 3g / 10min (190°C, 21.2N load)), reactive functional group content: 12% by weight

[0118] [(d) Other additives (d-1, d-2, d-3)] d-1: Polyethersulfone resin (Sumitomo Chemical Co., Ltd., SumikaExcel SE4800G), glass transition temperature: 225°C d-2: Glass fiber (T-747 manufactured by Nippon Electric Glass Co., Ltd.), average fiber diameter 13 μm d-3: Sodium phosphinate monohydrate (manufactured by Wako Pure Chemical Industries, Ltd.) In the following examples, material properties were evaluated by the following methods.

[0119] [Tensile test after immersion in hydrofluoric acid] Test pieces conforming to ISO527-2-1A were molded using an injection molding machine (Sumitomo Heavy Industries: SE75DUZ) at a cylinder temperature of 320°C and a mold temperature of 140°C. The obtained test pieces were immersed in hydrofluoric acid (50% aqueous solution) in a PFA container and treated at 60°C for 500 hours. Tensile tests (ISO527-1, 2) were performed on the immersed test pieces at an atmosphere of 23°C, a tensile speed of 50mm / min, and a chuck distance of 114mm, and the tensile elongation at break (nominal strain) was evaluated.

[0120] [Weld tensile test] Using an injection molding machine (Sumitomo Heavy Industries: SE75DUZ), the specimens were injection molded at a cylinder temperature of 300°C and a mold temperature of 150°C to obtain tensile dumbbell specimens (parallel part shape: thickness 1.6 mm, width 6 mm, gauge length 50 mm) with gates at both ends and a weld formed in the center. Using the obtained specimens, tensile tests were performed at a temperature of 23°C and a tensile speed of 10 mm / min to evaluate the tensile elongation at break, tensile strength, and tensile product. The tensile product was calculated by integrating the area under the stress-strain curve at every 0.04% elongation rate and the stress value.

[0121] [Weld tensile test at 80℃] A tensile dumbbell specimen prepared in the same manner as that used in the above weld tensile test was subjected to a tensile test at a temperature of 80° C. and a tensile speed of 10 mm / min to evaluate the tensile strength.

[0122] [Melt Viscosity] The melt viscosity of the PPS resin composition was measured using a capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. under conditions of 320° C. and a shear rate of 2432 / s. A capillary having a length of 10 mm and an aperture of 1 mm was used for the measurement.

[0123] [GPC measurement] Gel permeation chromatography (GPC) was used to determine the weight average molecular weight and number average molecular weight of the PPS resin composition and PPS resin calculated in terms of polystyrene, as well as the proportion of component (X) detected earlier than the elution time corresponding to the polystyrene-equivalent molecular weight of the PPS resin composition of 750,000, and the weight average molecular weight of component (Y) detected later than the elution time corresponding to the molecular weight of 750,000. The GPC measurement conditions are shown below. Equipment: SSC-7110 (Sensyu Science) Column name: Shodex UT806M x 2 Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL (slurry: approximately 0.2% by weight).

[0124] [Carboxyl group content of PPS resin] The carboxyl group content of the PPS resin was calculated using a Fourier transform infrared spectrometer (hereinafter abbreviated as FT-IR).

[0125] First, benzoic acid was measured as a standard substance by FT-IR, and the absorption of the C-H bond of the benzene ring at 3066 cm -1 The absorption intensity of the peak (b1) and the absorption of the carboxyl group at 1704 cm -1 The absorption intensity (c1) of the peak was read, and the amount of carboxyl groups per benzene ring unit (U1), (U1) = (c1) / [(b1) / 5], was calculated. Next, the PPS resin was melt-pressed at 320°C for 1 minute, and then quenched to obtain an amorphous film, which was then subjected to FT-IR measurement. -1 Absorption intensity (b2) and 1704cm -1The absorption intensity (c2) of the sample was read, and the amount of carboxyl groups per benzene ring unit (U2) was calculated as (U2) = (c2) / [(b2) / 4]. The carboxyl group content per 1 g of PPS resin was calculated using the following formula. Amount of carboxyl groups in PPS resin (μmol / g) = (U2) / (U1) / 108.161 × 1000000.

[0126] [Fluidity (Spiral Flow)] Using a 1mm thick spiral flow mold, molding was performed under the following conditions: cylinder temperature 320℃, mold temperature 140℃, injection speed 230mm / sec, injection pressure 98MPa, injection time 5sec, cooling time 15sec, and flow length was measured (injection molding machine used: Sumitomo Heavy Industries "SE-30D").

[0127] [Crack resistance] Injection molding was performed with a cylinder temperature of 320°C, a mold temperature of 130°C, an injection speed of 100 mm / s, and an injection pressure set within 50 to 80 MPa so that the filling time was 0.4 seconds (molding machine used: Sumitomo Heavy Industries, Ltd. "SE75DUZ-C250") to obtain an insulating component for batteries having an opening as shown in Figure 1 (size: length: 55 mm, width: 20 mm, thickness: 2 mm, opening size: 6 mmφ, weld line: 2 mm).

[0128] The resulting insulating material for batteries was bent 90 degrees with the weld line as the center line, and the state of damage was evaluated according to the following criteria: When 10 specimens were evaluated, a level with no breaks or cracks was judged as ◎, a level with no breaks and one or more but three or fewer cracks was judged as ○, a level with no breaks and four or more but ten or fewer cracks was judged as △, and a specimen with even one break was judged as ×.

[0129] [Resistance to hydrofluoric acid (weight change rate before and after immersion in hydrofluoric acid)] Using an injection molding machine (Sumitomo Heavy Industries: SE75DUZ), molded products conforming to ISO527-2-1A were molded under conditions of a cylinder temperature of 320°C and a mold temperature of 140°C. The weight of the obtained molded product was measured and recorded as the weight before treatment. The molded product was then immersed in hydrofluoric acid (50% aqueous solution) in a PFA container and treated at 60°C for 500 hours. After treatment, the aqueous solution on the surface was removed, and the weight of the molded product was measured and recorded as the weight after treatment. The weight change rate was calculated as the absolute value of (weight of molded product after treatment - weight of molded product before treatment) / weight before treatment x 100 (%).

[0130] [Examples 1 to 4, 6 to 8, Comparative Examples 1, 3 to 7] (a) PPS resin, (b) organic silane compound, (c) polyolefin monomer or polyolefin copolymer containing 80 wt% or more of olefin component, (d) other additives were dry blended in the ratio shown in Table 1, and then melt-kneaded using a Japan Steel Works TEX30α type twin-screw extruder (30 mmφ, L / D=45) equipped with a vacuum vent, with the screw arrangement set to three kneading parts, the ratio of the kneading part to the total screw length being 30%, the cylinder temperature set to 320°C, and the screw rotation speed set to 300 rpm. The melt-kneading method under these conditions is called A. Then, the mixture was pelletized using a strand cutter. The obtained pellets were dried overnight at 130°C and used for measuring melt viscosity and GPC. The obtained pellets were also subjected to injection molding, and evaluated for hydrofluoric acid immersion test, weld characteristics, moldability, and caulking resistance. The results were as shown in Tables 1 and 2.

[0131] [Example 5] Melt kneading was performed under the same conditions as in Example 1, except that the screw rotation speed was set to 500 rpm, to obtain resin composition pellets, and various characteristics were evaluated. The melt kneading method under these conditions is referred to as B. The results are shown in Table 1.

[0132] [Comparative Example 2] A side feeder was installed at a position 45% of the total length of the screw, and glass fibers were added using the side feeder. The melt-kneading was carried out under the same conditions as in Example 1, except that resin composition pellets were obtained and various characteristics were evaluated. The melt-kneading method under these conditions was designated as C. The results were as shown in Table 2.

[0133] [Table 1]

[0134] [Table 2]

[0135] The results of the above-mentioned Examples and Comparative Examples will be compared and explained.

[0136] In Examples 1 to 8, by using a PPS resin composition containing (a) PPS resin and (b) an organic silane compound, excellent tensile elongation at break after hydrofluoric acid immersion treatment and small weight change before and after hydrofluoric acid immersion treatment, which is a practical characteristic, were achieved. In addition, excellent tensile product was achieved in the weld tensile test, and the tensile elongation at break of the welds tended to be improved, especially compared to the comparative examples. In the Examples, the characteristics of the welds were excellent, so the crimping resistance as an insulating member was good.

[0137] (C) Examples 3 and 4, which contained an olefin copolymer and other additives, tended to show a larger change in weight before and after the hydrofluoric acid treatment than Examples 1 and 2. In addition, the tensile product and weld tensile breaking elongation in the weld tensile test decreased, and the crimping resistance tended to decrease.

[0138] On the other hand, the tensile elongation at break after immersion in hydrofluoric acid was small and the resistance to hydrofluoric acid was poor in Comparative Examples 1 to 6. In Comparative Example 2, the shape of the test piece was not retained after immersion, so measurement was not possible.

[0139] In addition, in all of Comparative Examples 1 to 6, the tensile product in the weld tensile test was small at 100 MPa·% or less, the toughness was low, and the molded articles were all broken in the caulking resistance test. The reason for this result is presumed to be that no organosilane compound was used in Comparative Example 1. In Comparative Example 2, glass fiber was used, and the toughness was extremely reduced. In Comparative Examples 3 to 5, which used a PPS resin with a low molecular weight, the proportion of component (X) in the GPC measurement was low, and the weight average molecular weight of component (Y) was also small. In Comparative Example 5, in which 0.1 parts by weight of an organosilane compound was blended, almost no effect of adding the organosilane compound was observed. On the other hand, in Comparative Example 7, in which 10 parts by weight of an organosilane compound was blended, the resin composition was significantly thickened, and a molded article could not be molded by injection molding. [Explanation of symbols]

[0140] 1. Molded product for evaluating crimping resistance 2. Gate 3. Opening 4. Weld lines

Claims

1. An insulating member for a battery, the insulating member being made of a polyphenylene sulfide resin composition containing (a) a polyphenylene sulfide resin and (b) an organosilane compound, the organosilane compound being an isocyanate group-containing alkoxysilane compound, the content of the organosilane compound being 0.2 to 5 parts by weight per 100 parts by weight of the total of the resin composition, the resin composition being injection molded into a test piece (ISO527-2-1A) and being immersed in hydrofluoric acid (50% aqueous solution) at 60° C. for 500 hours, the test piece having a tensile elongation at break of 5% or more in a tensile test (ISO527-1, 2), and the resin composition being subjected to a molecular weight distribution obtained by measurement by gel permeation chromatography (GPC), the weight average molecular weight of a component detected later than an elution time corresponding to a polystyrene-equivalent molecular weight of 750,000 being 50,000 to 95,000.

2. 2. The insulating material for a battery according to claim 1, wherein a test piece (ISO527-2-1A) obtained by injection molding the resin composition is immersed in hydrofluoric acid (50% aqueous solution) at 60° C. for 500 hours, and the weight change rate before and after immersion is 2% or less.

3. 3. The insulating member for a battery according to claim 1 or 2, wherein a test piece obtained by injection molding the resin composition has a thickness of 1.6 mm, a width of 6 mm, and a gauge length of 50 mm, and has a weld formed in the center between the gauge lines. In a tensile test performed at 23° C. and a tensile speed of 10 mm / min, the insulating member for a battery has a tensile product, which is represented by the area under the curve of the stress-strain curve, of 100 MPa·% or more.

4. The insulating member for a battery according to any one of claims 1 to 3, wherein a test piece obtained by injection molding the resin composition, the test piece having a thickness of 1.6 mm, a width of 6 mm and a distance between the gauge lines of 50 mm, and a weld portion formed in the center between the gauge lines, has a tensile breaking elongation of 3.0% or more in a tensile test measured under conditions of 23°C and a tensile speed of 10 mm / min.

5. The insulating member for a battery according to any one of claims 1 to 4, wherein a test piece obtained by injection molding the resin composition, the test piece having a thickness of 1.6 mm, a width of 6 mm and a distance between the gauge lines of 50 mm, and a weld portion formed in the center between the gauge lines, has a tensile strength of 45 MPa or more when the test piece is subjected to a tensile test under conditions of 80°C and a tensile speed of 10 mm / min.

6. 6. An insulating member for a battery according to claim 1, wherein the resin composition contains less than 1 part by weight of (c) a polyolefin monomer or polyolefin copolymer containing 80 wt% or more of an olefin component per 100 parts by weight of (a) PPS resin.

7. 7. The insulating member for a battery according to claim 1, wherein the melt viscosity of the resin composition (measurement conditions: temperature 320° C., shear rate 2432 / s) is 250 Pa·s or less.

8. 8. An insulating member for a battery according to any one of claims 1 to 7, wherein in the molecular weight distribution obtained by measuring the resin composition by gel permeation chromatography (GPC), the proportion of components detected earlier than the elution time corresponding to a polystyrene-equivalent molecular weight of 750,000 is 0.4 to 8.5%.

9. 9. The insulating member for a battery according to claim 1, wherein the proportion of the polyphenylene sulfide resin (a) in the resin composition is 95% by weight or more.

10. 10. The insulating member for a battery according to claim 1, having a weld line.

11. 11. A method for producing an insulating member for a battery according to claim 1, comprising injection molding the resin composition.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP1996321326A

  • Polyarylene sulfide resin composition

    JP2001002920A

  • Nonaqueous electrolyte secondary battery

    JP2002231314A

  • Battery case

    JP2003331797A

  • Nonaqueous electrolyte battery

    JP2006147159A